Pengembangan Industri Kecil Menengah IKM Bisnis Inovatif Kota Surakarta - Emiliana Sri Pudjiarti; Endang Swastuti (Jurnal Pengabdian UNDIKMA, 2022)
This service aims to be strategic for increasing regional competitiveness and developing the economy of the City of Surakarta. The method that will be used in this service is the Analytical Hierarchy Process (AHP) method. Partners in this competition are business SMEs in Surakarta City. Based on the determination of Leading Priority SMIs using the AHP approach, the leading order for Innovative Business SMIs in Surakarta City is as follows; (1) Fashion, (2) Culinary, (3) Fine Arts, (4) Crafts, (5) Design, (6) Performing Arts. The results of this service are in the form of a priority order of efforts to build, develop, and manage Innovative Business SMIs in Surakarta City, where the Leading Priority Innovative Business SMIs will be the "locomotive" to grow and develop Innovative Business SMIs in Surakarta City as a whole.